2012
DOI: 10.1111/j.1582-4934.2012.01655.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac telocytes were decreased during myocardial infarction and their therapeutic effects for ischaemic heart in rat

Abstract: Recently, cardiac telocytes were found in the myocardium. However, the functional role of cardiac telocytes and possible changes in the cardiac telocyte population during myocardial infarction in the myocardium are not known. In this study, the role of the recently identified cardiac telocytes in myocardial infarction (MI) was investigated. Cardiac telocytes were distributed longitudinally and within the cross network of the myocardium, which was impaired during MI. Cardiac telocytes in the infarction zone wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
131
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(151 citation statements)
references
References 32 publications
(46 reference statements)
16
131
0
4
Order By: Relevance
“…Moreover, expression of angiogenic VEGF and NOS2 was observed in the border zone of MI in TCs located in the close proximity to capillaries (41). Additionally, cytochemical analysis of TCs located in the muscular stem cell niche demonstrated expression of endoglin (CD105), which is a vascular proliferation marker (48).…”
Section: Markers Of Vascular Tcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, expression of angiogenic VEGF and NOS2 was observed in the border zone of MI in TCs located in the close proximity to capillaries (41). Additionally, cytochemical analysis of TCs located in the muscular stem cell niche demonstrated expression of endoglin (CD105), which is a vascular proliferation marker (48).…”
Section: Markers Of Vascular Tcsmentioning
confidence: 99%
“…Among them, myocardial infarction (MI) can be mentioned. TCs are particularly prone to ischaemia and hence their network is almost completely destroyed due to MI (41). Other conditions connected with TCs depletion are dilated, ischaemic and infl ammatory cardiomyopathies as well as cardiac manifestation of systemic sclerosis (15,30).…”
Section: Role Of Cardiac Tcs In Pathological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has indicated that TCs are involved in the pathological processes of many diseases, including myocardial infarction (Manole et al, 2011;Zhao et al, 2013Zhao et al, , 2014, heart failure (Richter and Kostin, 2015), renal ischemia-reperfusion injury (Li et al, 2014), liver fibrosis (Fu et al, 2015), and others. However, the potential roles and mechanisms of TCs in the repair of vascular injury remained to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrastructurally, these cells are characterized by degenerative processes including cytoplasmic vacuolization, shrinkage, and shortening of the cytoplasmic prolongations (telopodes). The reduced number of cardiac telocytes was also described during experimental myocardial infarction in rats (Zhao et al 2013). …”
Section: Cardiac Telocytes During Different Pathological Conditionsmentioning
confidence: 99%